Evaluation of Rational Antibiotic Use (RAU) in Cerebrovascular Accident (CVA) Patients in the ICU Using the Gyssens Criteria - Prasetyawan, Fendy; Saristiana, Yuneka; Savitri, Lisa; Salmasfattah, Novyananda; Ilmi, Tsamrotul; Herman, Herman (Transpublika Publisher, 2025)
Cerebrovascular accident (CVA) is a major cause of morbidity and mortality, often requiring intensive care unit (ICU) treatment. Patients with CVA are at high risk for secondary infections, which commonly lead to the use of antibiotics. This study aimed to evaluate the patterns and rationality of antibiotic use in CVA patients treated in the ICU of a regional hospital using the Gyssens method. A retrospective observational study was conducted involving 30 CVA patients who received antibiotics during their ICU stay. Data collected included patient demographics, comorbidities, types of antibiotics used, route of administration, combination patterns, and evaluation of prescription rationality based on the Gyssens criteria. The most frequently used antibiotic class was third-generation cephalosporins (60%), with ceftriaxone being the most prescribed (46.7%). All antibiotics were administered intravenously. Combination therapy was used in 20% of cases. Based on Gyssens categorization, only 33.3% of prescriptions were considered rational (category 0). The remaining 66.7% were irrational, including delayed initiation or discontinuation (13.3%), incorrect dosing (16.7%), unnecessarily broad-spectrum (10%), and no indication (6.7%). The study highlights a substantial proportion of irrational antibiotic use in ICU CVA patients, mainly due to suboptimal timing, dosing errors, and unnecessary broad-spectrum antibiotics. These findings underline the importance of antimicrobial stewardship and routine rationality assessments to ensure optimal antibiotic use and patient outcomes.